2011
DOI: 10.1080/02786826.2011.582193
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Automated Electrostatic Sampler (AES) for Bioaerosol Detection

Abstract: In this study, an automated bioaerosol collection and output system was developed using a new electrostatic sampling method. The electrostatic sampler was designed using a half-ball shape steel electrode (radius is 45 mm) with three aerosol inlets (radius is 3.5 mm) on the top and a copper plate electrode (6 and 16 mm in diameter) suited inside a circular plastic support. Above the plate electrode, a plastic cylindrical reservoir (14 mm in diameter and 1 mm in height) was built with liquid inlet and outlet mad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 20 publications
(29 reference statements)
0
58
0
Order By: Relevance
“…Each have their own advantages and disadvantages and these should be investigated thoroughly by the individual investigator. Electrostatic (Mainelis et al, 1999(Mainelis et al, , 2002Tan et al, 2011) and thermal precipitators (Kethley et al, 1952;Orr et al, 1956) have been developed in an attempt to collect viable aerosols with less damaging force. Recently, methods for online detection of biological aerosols have been developed using a variety of optical and additional techniques.…”
Section: Pbap Sampling Methodsmentioning
confidence: 99%
“…Each have their own advantages and disadvantages and these should be investigated thoroughly by the individual investigator. Electrostatic (Mainelis et al, 1999(Mainelis et al, , 2002Tan et al, 2011) and thermal precipitators (Kethley et al, 1952;Orr et al, 1956) have been developed in an attempt to collect viable aerosols with less damaging force. Recently, methods for online detection of biological aerosols have been developed using a variety of optical and additional techniques.…”
Section: Pbap Sampling Methodsmentioning
confidence: 99%
“…In comparison with results from Tan et al (2011), the relative collection efficiency of our ESP sampler was consistently ϒ relative = (1-n ESPoff / n ESPon ) ≈ 100%, without the large variations, ϒ relative = 70% -90%, seen from their sampler.…”
Section: Resultsmentioning
confidence: 95%
“…Similarly, Han & Mainelis [41] introduced an ESP sampler for bioaerosols, mainly targeting airborne pathogens and microorganisms, by collecting rolling water droplets off the collection electrode. Tan et al [42] proposed an airborne bacteria sampler using a semi-spherical electrostatic precipitator, and reported varying relative collection efficiencies, ϒ ESPon/ESPoff , from 50% to 100%, where the total capture was compared with that when no voltages were applied to the ESP electrodes. The collection was dependent on applied voltages, flow rates, particle sizes and geometrical design parameters.…”
Section: Introductionmentioning
confidence: 99%
“…However, interest in electrostatic methods is growing and studies recently showed that it is a suitable method to collect microorganisms (Table 1). Compared to collection by impaction methods, advantages of the electrostatic-sampling-based method are lower impaction stress (Mainelis et al 1999), lower pressure drop and lower power consumption (Tan et al 2011). Yao demonstrated that electrostatic sampling could achieve culturable bioaerosol concentration levels as much as nine times higher than the BioStage impactor (Yao and Mainelis 2006) and five to ten times higher airborne allergen and toxin concentration levels than the BioSampler (Yao et al 2009).…”
Section: Introductionmentioning
confidence: 99%